Penerapan Metode Survey, Question, Read, Recite, And Review (SQ3R) Untuk Meningkatkan Keterampilan Membaca Siswa Kelas III SD Negeri Panaikang Kabupaten Gowa - Khaerunnisa Khaerunnisa; Syamsuryani Eka Putri Atjo; Nur Zalsha Zasikha (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims to determine the application of the Survey, Question, Read, Recite, And Review (SQ3R) Method to improve the reading skills of grade III students of SD Negeri Panaikang, Gowa Regency. This research is a class action study. This research was carried out in class III of SD Negeri Panaikang Gowa Regency in the even semester of the 2021/2022 academic year. The data analysis techniques carried out are qualitatively and quantitatively. Qualitatively, the data were analyzed from the results of observations of teacher performance and student learning activities. Meanwhile, as qualitative, the data is analyzed from the results of tests carried out at the end of each cycle. The results showed that in the first cycle the teacher's teaching activity was in the sufficient category and in the second cycle increased to a good category. And students' reading skills also improved, in the first cycle it was in the sufficient category and in the second cycle it increased to a good category. From the results of the study, concluded that the application of the Survey, Question, Read, Recite, And Review (SQ3R) Method can improve the reading skills of grade III students of SD Negeri Panaikang, Gowa Regency has been successful.